2018
DOI: 10.1111/jgh.14000
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged azathioprine treatment reduces the need for surgery in early Crohn's disease

Abstract: Prior bowel resection, smoking, and hemoglobin < 110 g/L at the time of initiation of AZA were risk factors associated with intestinal surgery in patients with early CD. However, prolonged use (≥ 36 months) of AZA was associated with a more favorable disease course of early CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…[21][22][23] In this study, previous different previous intestinal surgery rates did not seem to affect baseline LI, whereas intestinal reception was one of the most decisive and scoring items in LI. During the follow-up period, the CD-related bowel resection rate was 14.3%, which was similar to certain previous studies, 24,25 but lower than that in other studies. 26,27 Patients with longer disease duration tended to have a higher intestinal surgery rate than patients with early CD (20.2% vs. 7.1%, P = 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…[21][22][23] In this study, previous different previous intestinal surgery rates did not seem to affect baseline LI, whereas intestinal reception was one of the most decisive and scoring items in LI. During the follow-up period, the CD-related bowel resection rate was 14.3%, which was similar to certain previous studies, 24,25 but lower than that in other studies. 26,27 Patients with longer disease duration tended to have a higher intestinal surgery rate than patients with early CD (20.2% vs. 7.1%, P = 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, previous different previous intestinal surgery rates did not seem to affect baseline LI, whereas intestinal reception was one of the most decisive and scoring items in LI. During the follow-up period, the CD-related bowel resection rate was 14.3%, which was similar to certain previous studies, [ 24 , 25 ] but lower than that in other studies [ 26 , 27 ]. Patients with longer disease duration tended to have a higher intestinal surgery rate than patients with early CD (20.2% vs. 7.1%, P = 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…Even though some observational studies showed no benefits, [ 4 , 19 , 37 , 39 , 42 ] 1 meta-analysis [ 5 ] and other observational studies did show benefit of early use in reducing CD-related surgeries. [ 11 , 17 , 18 , 20 , 23 , 32 , 34 , 38 , 40 , 43 ] In this cohort, we performed subgroup analysis to determine this effect. To ensure the benefits of thiopurines, only those who took the medicine for at least 3 months were included.…”
Section: Discussionmentioning
confidence: 99%